Tyre forces estimation for off-road motorcycles. (March 2021) - Vasquez, F.; Lot, R.; Rustighi, E.; Pegoraro, R.
Highlights: Tyre contact forces of an off-road motorcycle are estimated from kinematics. Estimated contact forces vary consistently with track obstacles. Estimator detects wheel detachments, whoops braking and riding variations. Abstract: Off-road motorcycles transit over significantly irregular terrains facilitated by their suspension system. The optimisation of their suspension is an open topic. On one hand, on-road motorcycles need to be extended to consider off-road peculiarities such as larger amplitude of motion and a standing rider, to provide optimisation predictions. On the other hand, an objective methodology to verify the predictions is needed since the current practice is to rely on the subjective perception of the rider. In this article, we addressed for the first time, the second problem by developing an estimator of contact forces based on inverse dynamics equations and kinematic measurements. First, in a virtual experiment, it was verified that the estimation is satisfactory. Subsequently, using data recorded at a motocross track, we showed that the estimated forces vary consistently with the obstacles in the track. This provides an objective and consistent indication of the performance of the motorcycle and hence can be used to verify optimisations.